Rearing in an envy-like environment increases anxiety-like behaviour in mice - Ueno Hiroshi; Kitano Eriko; Takahashi Yu; Mori Sachiko; Murakami Shinji; Wani Kenta; Matsumoto Yosuke; Okamoto Motoi; Ishihara Takeshi (Translational Neuroscience, 2025)
Interest in the societal and psychological harm caused by widespread envy and social comparison is increasing. Envy is associated with anxiety and depression, though the mechanism by which envy affects neuropsychiatric disorders, such as depression, remains unclear. Clarifying the neurobiological basis of envy’s effects on behaviour and emotion regulation in experimental mice is essential for developing disease-prevention and treatment strategies. As mice recognize other mice in neighbouring cages, this study investigated whether they recognize neighbouring cages housed in environmentally enriched cages and suffer psychological stress due to envy. After being raised in an envy-like environment for 3 weeks, we revealed changes in the behaviour of the mice through a series of behavioural experiments. Mice raised in an envious environment showed increased body weight and anxiety-like behaviour but decreased social behaviour and serum corticosterone levels compared to control mice. Thus, mice recognize their neighbouring cages and experience psychological stress due to envy. This study revealed a part of the scientific basis for why envy increased anxiety. Using this novel experimental breeding environment, it may be possible to create an experimental animal model of anxiety disorders.